Post Covid-19 Reflection from Indonesian EFL Students on Their Learning Autonomy - Ariawan, Soni; Syarifudin; Zaikalina, Rabbania (The Art of Teaching English as a Foreign Language (TATEFL), 2024)
Distance learning is an alternative way to reduce the spread of the Covid-19 pandemic. In this situation, learning was conducted through electronic media and internet connection independently. So, in this case, students must take the initiative to understand the material without having a face-to-face guide from the teacher which might increase their learning autonomy. This research aims to examine students’ reflections on how they learned English autonomously during the Covid-19 pandemic unveil the perception of learner autonomy, and find out the factors that influence learner autonomy after experiencing distance learning. The present research implemented a mixed-method of research design by administering the questionnaire and conducting a semi-structured interview. The respondents were the students of the English Language Education Study Program at the State Islamic University of Mataram. The findings showed that students gain autonomy in English learning by utilizing the internet resources optimally, such as YouTube, Google, social media, and learning applications during distance learning. They also have a very positive response to learning autonomy, in terms of the role of the learner, the role of the lecturer, the type of task, and the role of the environment